Knowledge, Attitude and Practice of Iranian Women towards Breast Cancer Screening Methods - Bahar Morshed Behbahani (Intelektual Pustaka Media Utama, 2017)
Female breast cancer is the second leading cause of death due to cancer and the second leading cause of cancer deaths in women after lung cancer. This study aimed to investigate the knowledge, attitude and practice of women about breast cancer’s screening methods in order to offer more appropriate training programs if necessary. A cross-sectional study was carried out with a population comprised of women who had referred to public health centers in Sanandaj in 2008. The results of this study do provide some understanding on the topic and suggest that although the majority of Iranian women seem to be quite knowledgeable about breast cancer and screening methods. They need more education on breast cancer, SBE and other methods of early detection. We recommend the establishment of an institutional framework and policy guidelines that will enhance adequate and urgent information dissemination about breast cancer and screening methods to all women in Iran. Since women’s beliefs and behaviors may impact young women, designing training courses for this group seems to be essential.